The experience in the research and design of a 2 million tons/year flue gas CO2 capture project for coal-fired power plants. (September 2021) - Lu, Shijian; Fang, Mengxiang; Li, Qingfang; Chen, Hongfu; Chen, Fu; Sun, Wentan; Wang, Hui; Liu, Haiyan; Zhang, Jian; Zhang, Xinjun; Liu, Haili
Highlights: The world's largest carbon capture projects from flue gas of coal power plants of Shengli oilfield 2 million tons/year of flue gas CO2 capture project is introduced. The blend amine absorbent performance, chemical absorption process, energy-saving method, and the layout area of engineering were interpreted. The health, safety, and environmental affect was analyzed and economic analysis was also carried out. The conclusion showed that the project has technical and economic feasibility. It is a comprehensive introduction of large-scale CO2 capture process and parameters. The energy consumption level of regeneration reaches the leading level of flue gas CO2 capture demonstration project. New energy-saving process of "interstage cooling + MVR heat pump + desorption heat energy recovery" is applied, and comprehensive regeneration energy consumption is less than 2.2 GJ/tCO2 . The level of total energy consumption is advanced in the world. The study showed that the total energy consumption per unit product is 121.4 kg (standard coal equivalent (SCE))/tCO2, which reduces the net CO2 emission by 1.3687 million tons per year. Abstract: The world's largest 2 million tons/year CO2 capture project from flue gas of coal power plants for EOR at Shengli oilfield of China was introduced. The blend amine absorbent performance, chemical absorption process, energy-saving method, and the layout area of engineering were interpreted. The health, safety, and environmental affect was analyzed and economic analysis was also carried out. The conclusion showed that the project has technical and economic feasibility. The study showed that the total energy consumption per unit product is 121.4 kg (standard coal equivalent (SCE))/tCO2, and the comprehensive regeneration energy consumption of the project is less than 2.2GJ/tCO2 . The total investment of the project is 1329.4 million CNY; the after-tax internal rate of return reaches 8% when the ex-factory price of CO2 is 301.84 CNY /t(excluding tax).